THE PSYCHOLOGICAL CONCEPTS IN TAYLOR SWIFT'S "BLANK SPACE" - Anindhita, Novia Putri (LANTERN (Journal on English Language, Culture and Literature), 2016)
“Blank Space” is a song that is sung by a singer, Taylor Swift. The lyrics tell about the lonely woman who dates a lot but always fails to manage her relationship. However, it does not make her worry to start a new relationship. The purpose of this study is to analyze the elements of the poetry in the lyrics and to show the readers the psychological contents as portrayed in the music video. The study uses intrinsic and extrinsic theories to analyze the data and library research to compile the data. Library research is used to get literary theories and psychological theories of Sigmund Freud.The finding of this study is the existence of psychoanalysis contents in American pop music included Id, ego, superego, defense mechanism act, and symbolization reflected in lyrics and scenes in the song and in the music video of  “Blank Space”